+0  
 
0
112
1
avatar

3x- 7x2 - 7x + 3 = 0

Guest Jun 1, 2017
Sort: 

1+0 Answers

 #1
avatar
0

Solve for x:
3 x^3 - 7 x^2 - 7 x + 3 = 0

The left hand side factors into a product with three terms:
(x - 3) (x + 1) (3 x - 1) = 0

Split into three equations:
x - 3 = 0 or x + 1 = 0 or 3 x - 1 = 0

Add 3 to both sides:
x = 3 or x + 1 = 0 or 3 x - 1 = 0

Subtract 1 from both sides:
x = 3 or x = -1 or 3 x - 1 = 0

Add 1 to both sides:
x = 3 or x = -1 or 3 x = 1

Divide both sides by 3:
Answer: | x = 3          or x = -1            or x = 1/3

Guest Jun 1, 2017

2 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details